“I Was Also Dying Silently...”: Black Graduate Students’ Mentorship Experiences at a University in Western Canada - Opini, Bathseba; Henry, Annette (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
This discussion examines the mentoring experiences of Black graduate students enrolled in a Faculty of Education at a university located in western Canada between the years 2010 and 2020. The students were pursuing masters’ and doctoral degrees and were asked to reflect on the mentorship and support that they received during the course of their graduate programs. Drawing from critical and interdisciplinary perspectives about Blackness, the paper analyzes these experiences as narrated by the participants through semi-structured qualitative research interviews. Findings point to the pervasiveness of systemic racism in a culture of whiteness, along with the lack of mentorship and its impacts on the Black graduate experience. The discussion concludes with recommendations for policy and practice.